2009
DOI: 10.1161/circulationaha.109.880385
|View full text |Cite
|
Sign up to set email alerts
|

γ-H2AX Foci as a Biomarker for Patient X-Ray Exposure in Pediatric Cardiac Catheterization

Abstract: Background-A better knowledge of patient x-ray dose and the associated radiation risk in pediatric interventional cardiology is warranted in view of the extensive use of x-rays and the higher radiosensitivity of children. In the present study, ␥-H2AX foci were used as a biomarker for radiation-induced effects. Patient-specific dose was assessed and radiation risks were estimated according to the linear-no-threshold model, commonly used in radiation protection, and the ␥-H2AX foci data. Methods and Results-In 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 40 publications
(51 reference statements)
14
103
2
Order By: Relevance
“…An increase in DSB was likewise shown after cardiac catheterization in children; the induced γ-H2AX foci in the low-dose range up to 5 mGy, however, correlated non-linearly with the blood dose determined using Monte Carlo simulation. In this instance the authors, similarly to the CT studies above, presume hypersensitivity in the low-dose range [24]. Two other studies demonstrated that the repair kinetics of DSB should be taken into account, especially due to fractionated radiation exposure during intervention, otherwise a repair-related underestimate of the actual radiation damage will result.…”
Section: Dsb After Angiographymentioning
confidence: 88%
See 1 more Smart Citation
“…An increase in DSB was likewise shown after cardiac catheterization in children; the induced γ-H2AX foci in the low-dose range up to 5 mGy, however, correlated non-linearly with the blood dose determined using Monte Carlo simulation. In this instance the authors, similarly to the CT studies above, presume hypersensitivity in the low-dose range [24]. Two other studies demonstrated that the repair kinetics of DSB should be taken into account, especially due to fractionated radiation exposure during intervention, otherwise a repair-related underestimate of the actual radiation damage will result.…”
Section: Dsb After Angiographymentioning
confidence: 88%
“…This quantity of radiation-induced foci demonstrate a dependence on the dose, which in most in-vitro and in-vivo studies was linear [7, 9,13,23,33]. Individual studies described non-linear relationships [14,15,24]. However, it should be noted that in this working group, the baseline values were higher by a factor of 10 ( • " Table 1).…”
mentioning
confidence: 86%
“…For example, gH2AX focus quantification has been used to assess the risk of exposure to ionizing radiation during clinical computed tomographic scans (59)(60)(61)(62) and to estimate the dose during radiotherapy (63)(64)(65) or in case of radiation accidents (66). Infrastructures for high-throughput biodensitometry screening after a radiologic event have been developed based on the gH2AX assay (67), and the European Biodosimetry Network is conducting large studies to evaluate the use of gH2AX focus quantification as a risk assessment tool in such cases (68).…”
Section: Reevaluation Of the Most Commonly Used Dsb Markermentioning
confidence: 99%
“…Gamma-H2AX foci analysis was used as a biomarker for individual radiation damage in pediatric patients undergoing cardiac catherization showing that previous estimates according to linear-no-treshold hypothesis have been underestimating radiation damage. Therefore, gamma-H2AX foci analysis could be used as a tool for estimations of DNA-damage effects after cardiac catherization (Beels, Bacher et al 2009). Another study showed that the amount of gamma-H2AX foci in lymphocytes after coronary CT angiography correlates to dose-length product (DLP) which is a physical parameter used to calculate delivered dose after CT.…”
Section: Wwwintechopencommentioning
confidence: 99%